Molecular responses to thermal streá in woody plants - Gomez, L.=700 1 Allona, I.; Ramos, A.; Ibañez, C.; Casado, R.; Arangoncillo, C.
(Es, En)
ilus., 109 ref.
Keywords: PLANTAS LEÑOSAS; CLIMATOLOGIA; ADAPTACION<<FRIO; DORMICION; ESPAÑA; CHOQUE DE CALOR